Static tensile test of metal alloys - Zeng, Guanliang (Nanyang Technological University, 2022)
The objective of this FYP is to fabricate test specimens and to conduct tensile tests according to the American Society for Testing and Materials (ASTM) guidelines. Another objective of this FYP is to determine the effects of varying the thickness of the specimen on the mechanical properties of the aluminium 6061-T6. This was done by plotting the Stress-Strain Curve from the raw data obtained from the test results and conducting analysis on the curve. In addition, the author had tried different testing methods such as using video extensometer and strain gauges to obtain strain readings to determine if the testing results will vary greatly. Lastly, recommendations on how to achieve reliable experiment results and other areas of research to look into will also be discussed.